Two new species of Cryptoperla (Plecoptera: Peltoperlidae) from China, with description of the nymph of Cryptoperla dui Sivec - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2018)
Two species of the peltoperlid genus Cryptoperla Needham, C. dactylina Du, sp. nov. and C. nangongshana Huo & Du, sp. nov. are described as new to science from Yunnan and Shaanxi provinces of China. Cryptoperla dactylina is characterized by a finger-like sclerotized projection with small-rounded processes on the first cercal segment and C. nangongshana is characterized by clusters of long bristles on the first six cercal segments. Additionally, a description of the nymph of C. dui Sivec is provided.